2015
DOI: 10.1007/s10482-015-0629-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of formate in combatting oxidative stress

Abstract: As all aerobic organisms are exposed to oxidative stress, they are known to devise intricate mechanisms to counter reactive oxygen species (ROS). Metabolic networks contributing to the production of ketoacids are prominent in alleviating the oxidative burden. When glyoxylate detoxifies ROS, formate is the principal by-product generated.In this study the contribution of formate in enabling the survival of the microbe Pseudomonas fluorescens challenged by hydrogen peroxide (H2O2) has been elucidated.When grown i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 59 publications
3
28
0
Order By: Relevance
“…Furthermore, the existing study established that oxidative stress affects metabolism via multiple mechanisms (Noctor, Lelarge‐Trouverie, & Mhamdi, ). Our results suggest that the MA‐induced oxidative stress depletes the release of formate, as previous study demonstrated that cells release formate when encountering oxidative stress (Jong, Azuma, & Schaffer, ; Thomas, Alhasawi, Auger, Omri, & Appanna, ). Furthermore, the significant elevations in acetoacetate observed in the medium‐dose group suggest MA induces lipid peroxidation (Jain, Kannan, & Lim, ).…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, the existing study established that oxidative stress affects metabolism via multiple mechanisms (Noctor, Lelarge‐Trouverie, & Mhamdi, ). Our results suggest that the MA‐induced oxidative stress depletes the release of formate, as previous study demonstrated that cells release formate when encountering oxidative stress (Jong, Azuma, & Schaffer, ; Thomas, Alhasawi, Auger, Omri, & Appanna, ). Furthermore, the significant elevations in acetoacetate observed in the medium‐dose group suggest MA induces lipid peroxidation (Jain, Kannan, & Lim, ).…”
Section: Discussionsupporting
confidence: 74%
“…Second, it could reveal the impact of H 2 O 2 on the C1 metabolism; it is known that C1 compounds can be transformed by cloud microorganisms (Husàrovà et al, 2011;Vaitilingom et al, 2010Vaitilingom et al, , 2011Vaitilingom et al, , 2013. In addition, Thomas et al (2016) report the overproduction of formate in a strain of Pseudomonas fluorescens exposed to H 2 O 2 . Indeed, formate contributes to the anti-oxidant strategy of this bacterium to supply NADH, which is known to be decreased under oxidative conditions.…”
Section: Discussionmentioning
confidence: 99%
“…; Thomas et al . ). Combined with observations that ketoacids can undergo non‐enzymatic decarboxylation in the presence of oxidizing agents (Bunton ; Mallet and Sun ; Mailloux et al .…”
Section: Ketoacids—the Extended Role Of Metabolism In Combatting Rosmentioning
confidence: 97%
“…; Thomas et al . ). Indeed, there are numerous, known and likely undiscovered, ketoacids that can be generated through the diverse metabolic pathways in prokaryotes.…”
Section: Ketoacids—the Extended Role Of Metabolism In Combatting Rosmentioning
confidence: 97%
See 1 more Smart Citation